A proteomic study of the effect of UV-B on the regulatory mechanism of flavonoids metabolism in pea seedlings - Fu, Xin; Xu, Yinghao; Lu, Ming (Frontiers in Nutrition, 2023)
UV irradiation is gradually being applied to sprouted food for sterilization. This study aimed to investigate the mechanism of response of pea seedlings to UV-B stress. Pea seedlings were treated with UV-B. We examined the growth status before and after treatment and conducted proteomic analysis. The results showed that the ascorbic acid content of UV-B-irradiated pea seedlings increased by 19.0%; the relative content of flavonoids increased by 112.4%; the length of edible parts decreased by 14.2%, and the elongation of roots increased by 11.4%. Further proteomic studies focusing on the flavonoid metabolism revealed significant increase in the levels of CHI, F3'5'H, F3H, F3'H, C4H, and CHR, the key enzymes for flavonoid synthesis. RT-qPCR indicated that the expression of the regulatory genes of these enzymes was significantly upregulated. This study provided a basis for further studies on the flavonoid response mechanism in pea seedlings during UV stress.